Surgical Plate Fixation of Simple Rib Fractures: A Case Report - Ronald Winardi Kartika (Journal of International Surgery and Clinical Medicine, 2022)
Introduction:  Rib fractures can cause patient morbidity that causes long hospitalization if conservative treatment is carried out. Current international guidelines recommend a minimally incisional surgical-based treatment approach to reduce pain and provide optimal clinical benefit. Numerous studies have demonstrated that surgical fixation in conjunction with multidisciplinary integrated care pathways offers the highest therapeutic benefit for developing countries, which are typically more accountable for a higher share of unfavorable global outcomes. This case report describes the selection of appropriate decision-making in the management of multiple rib fractures. Case description: We report that a 51-year-old, still actively working young female came to our emergency department after a motorcycle accident, left chest hitting the road boundary, 2 days earlier. He presented with severe upper chest pain, chest deformity, mild dyspnea, tachycardia, subcutaneous emphysema, and hematoma. The chest radiograph shows a hypo ventilated lung field and a minor pleural effusion. A computed tomography scan showed right lateral rib fractures 3–4 posterior and 5–6 posterolateral, with areas of hyperdensity of simple bone fragments, and pulmonary contusion. Treatment consists of minimal incision with surgical fixation of the 5th and 6th posterolateral ribs which causes pain. For rib fractures 3-4, because it is stable and protected by the scapula, we only perform conservative measures. Rib fixation uses titanium reconstruction plates and cortical fixing screws. The patient's clinical condition improved rapidly postoperatively with a length of stay of 2 days after surgery. Follow-up at 6 weeks, the patient confirmed a full return to preoperative daily activities with the return to normal work activities as well as high quality of life. Conclusion: In this case report, reported that in rib fractures in a developing country, thoracic trauma can be treated through medical treatment with minimal incisions which allows rapids recovery of the patient.